An exploratory study of universal design in relation to chemistry laboratory classroom design - Mariano, Ruth Denise Z.
ABSTRACT This study aimed to explore Universal Design principles in the chemistry laboratory classroom and its potential to address problems encountered by students with myopia. It first identified problems that myopic students were subjected to in the laboratory and the specific requirements that were needed in the room in order to associate the principles namely flexibility of use, perceptible information, and tolerance for error. The researcher used exploratory research design, whereby problems that myopic students encounter, laboratory classroom design, and universal design principles in the study was delved into, comprehending and clarifying each data in order to make a new discovery. Using qualitative and quantitative methods for gathering data, the researcher dissected the problems discovered and interjected each in the categorized requirements of a laboratory classroom in order to make sure of the consistency of the study and to organize the analysis. Survey questionnaires and a site observation sheet were used as key instruments in the study. Purposive sampling method was used in gathering data were the respondents are myopic junior and senior students from the institute of chemistry with the intention of getting students who are accustomed with chemical laboratory practice. The number of myopic students acquired during the study was twenty-two. The result of the analyzed data showed that although minimal, myopic students experienced problems in the chemical laboratory classroom both in architectural design and management. Factors of the universal design principles? flexibility of use, perceptible information and tolerance for error was seldom present in the laboratory studied or lacked proper treatment. It then denotes the need for reevaluation of laboratory design and whether it caters to students with myopia. For further study, the researcher highly suggests the study of non-myopic students, depth-perception or a study of work-furniture used in the laboratory classroom.